Potential Functions of the Gut Microbiome and Modulation Strategies for Improving Aquatic Animal Growth - Zhimin Zhang; Qiushi Yang; Haokun Liu; Junyan Jin; Yunxia Yang; Xiaoming Zhu; Dong Han; Zhigang Zhou; Shouqi Xie (Reviews in Aquaculture, 2025)
The increase in the body weight of animals, a pivotal indicator closely tied to production, is important to the aquaculture industry. Despite remarkable variability in gut microbiomes, which are intricately associated with their hosts and affect overall performance, fitness, and physiological outcomes, across individuals and species, the development and practical application of gut microbiota modulation in aquaculture remain underdeveloped. In this review, we systematically examine the advancements with a focus on the gut microbiomes of aquatic animals with different growth rates by literature search, summarizing the existing knowledge regarding the diversity, composition, and significance of the microbiome in individual growth. The comparative analysis reveals substantial alterations in the gut microbiome that correspond to changes in the growth rate of aquatic animals, with a species bias toward more carnivorous fish, and shrimps and sea cucumbers in nonfish species. The present review also discusses comparative gut microbiome research in aquaculture as an emerging field with great potential for advancing our understanding of animal growth, screening candidate probiotics, and facilitating microbiome modulation strategies. Besides, the present gaps in the knowledge of the gut microbiome associated with the growth and production of farmed animals have been highlighted. We propose potential directions to address emerging challenges and opportunities in this field, such as priority effects on gut microbiome establishment, especially in the early stage, and screening of host‐derived probiotics across various aquatic animals. Finally, we provide a conceptual framework for enhancing animal farming practices in aquaculture through intensified gut microbiome research.